ChemInform Abstract: Direct Arylation/Alkylation/Magnesiation of Benzyl Alcohols in the Presence of Grignard Reagents via Ni‐, Fe‐, or Co‐Catalyzed sp3 C—O Bond Activation. Issue 9 (5th March 2013) - Yu, Da‐Gang; Wang, Xin; Zhu, Ru‐Yi; Luo, Shuang; Zhang, Xiao‐Bo; Wang, Bi‐Qin; Wang, Lei; Shi, Zhang‐Jie
Abstract A broad spectrum of transformations is investigated in the presence of the different catalytic systems.